PENGARUH INTERVAL PEMBERIAN AIR KELAPA DAN APLIKASI PUPUK KANDANG KOTORAN SAPI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TOMAT (LYCOPERSICUM ESCULENTUM MILL) - Moh Rifky abdurahman Gani; Yunnita Rahim; Fitriah Suryani Jamin (Universitas Negeri Gorontalo, 2022)
Tomato (Lycopersicum esculentum Mill) is the most popular agricultural product with a high economic value in society. Thus, this study aims to determine the effect and interaction of adding coconut water and cow manure on the growth and yield of tomato plants. This research was conducted from August to October 2021 at Putri Mandiri Green House, Sipatana Subdistrict, Gorontalo City using a Factorial Completely Randomized Design (CRD). The interval of adding coconut water consisted of 3 levels, while the adding of cow dung manure consisted of 4 levels. The results of this study indicated that the interval of adding coconut water and cow manure affected the growth and yield of tomato plants. It is further explained by the following results: 1) The interval of giving coconut water every 8 days has an effect on plant height, 2) The treatment once every 4 days has an effect on the number of leaves of tomato plants, 3) The adding of cow manure in the treatment of 120 g polybag-1gave an effect on the number of leaves, number of fruits, and fruit weight per tomato plant, and 4) The treatment of 60 g polybag-1 had an effect on the fruit weight of tomato plants. Besides, the interaction of treatment intervals of adding coconut water and cow manure did not affect the growth and yield of tomato plants.Keywords: Tomato Plants, Coconut Water, Cow Manure